Pragmatic Study on Refusals Performed by Israeli NSHs and Egyptian HSL Learners - Ibrahim, Ahmed (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2026)
This study investigated the production of refusal strategies by Egyptian Hebrew learners as a second language (HSL). A total of 40 individuals participated in this study: 20 Israeli native Hebrew speakers (IHs) and 20 Egyptian HSL speakers (EHs). Based on Beebe et al. (in: Scarcella, Andersen, Krashen (eds) Developing communicative competence in second language, Newbury House, Cork, 1990) refusal taxonomy, data were collected using a Discourse Completion Task (DCT) that featured five different social situations in Hebrew to investigate the semantic formulas of refusal. The findings revealed diversity in the refusal strategies used by the Egyptian and Israeli groups, depending on which of the five scenarios they encountered. The results demonstrated that Egyptian Hebrew learners succeeded pragmatically in performing refusals. The results also showed that the participants from both groups most frequently utilized indirect refusal strategies, followed by direct strategies and adjuncts to refusals. Moreover, the findings indicate no evidence of pragmatic transfer between native and non-native Hebrew speakers.